Exploring the Artistic Representation of the Chinese National Spirit in Zhang Zhao’s Piano Work "Ballade - Singing the Little Cowboy" - Huang, ZiHeng; Rattanachaiwong, Nataporn (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: This study explores the life and works of Zhang Zhao, analyzes the compositional techniques of his modern national piano piece "Ballade - Singing the Young Cowherd," and investigates the manifestation of the Chinese national spirit in Zhang Zhao’s modern national piano works. This can enrich people’s understanding of the Chinese national spirit and provide new ideas for inheriting the Chinese national spirit and strengthening the consciousness of the Chinese national community. Materials and Methods: The literature research method involves consulting, analyzing, and integrating documents based on specific research objectives and topics to understand the current state of the research field and identify better research paths. The work analysis method involves collecting examples of works and analyzing aspects such as their form structure, harmonic texture, rhythm expression, and thematic variations, ultimately extracting the compositional techniques and elements of national style characteristics. This study will provide a detailed analysis and summarization of the characteristic entries of national music elements based on a broad review of relevant literature and examples of works from both domestic and international sources, offering references for further research. Results: Through the analysis of the work "Ballad - Singing the Little Cowherd," it is found that Zhang Zhao cleverly integrates elements of traditional Chinese music with Western musical structures, not only showcasing his profound musical skills but also inheriting and promoting the cultural essence of the Chinese nation. It reveals the innovative, patriotic, inclusive, harmonious, and resilient spirit embedded in the work. Conclusion: The modern national piano work "Ballade - Singing of the Little Cowherd Wang" by Zhang Zhao, with its unique artistic style and profound historical and cultural connotations, demonstrates the indomitable and hard-working spirit of the Chinese nation. This is not only an innovative interpretation of music but also an inheritance and promotion of the Chinese national spirit.